A PSYCHOLINGUISTIC ANALYSIS OF FIRST LANGUAGE INTERFERENCE IN ENGLISH PRONUNCIATION AMONG SENIOR HIGH SCHOOL EFL STUDENTS - Rahmatul Ummu Arifin (Scolae: Journal of Pedagogy, 2024)
First language (L1) interference is one of the main factors affecting English pronunciation among English as a Foreign Language (EFL) learners. This study aims to analyze the influence of first language interference on the English pronunciation of senior high school EFL students from a psycholinguistic perspective. Using a qualitative descriptive approach, data are collected through pronunciation tasks, oral reading, and interviews. The findings are expected to show that differences between the phonological systems of the first language and English lead to pronunciation errors, such as sound substitution and mispronunciation of unfamiliar phonemes. These findings provide insight into the cognitive processes involved in speech production and highlight the importance of appropriate pronunciation instruction to reduce L1 interference in EFL learning.